Nucleation enhancement behavior of diamond on Si substrate according to surface treatment materials - Park, BS; Baik, YJ (ELSEVIER SCIENCE SA LAUSANNE, 1997)
The dependence of diamond nucleation on pretreatment materials was investigated. Diamond, cubic boron nitride (c-BN), silicon carbide (SiC) and alumina (Al2O3) powders with an average particle size of 3 mu m were used for surface treatment. Si substrates are vibrated ultrasonically in a powder-acetone mixture and then cleaned in acetone. Diamond was deposited on the treated Si substrate by a tungsten filament: CVD (HFCVD) method under the following conditions: 40 mbar of pressure, 1% of methane in hydrogen, 800 degrees C substrate temperature. The nucleation density was decreased until saturated as the substrate cleaning time increased regardless of the substrate treatment material. However, the saturated nucleation density decreased in the order of diamond, c-BN, SiC and finally Al2O3. The residue of the treatment material on Si surface was detected after cleaning for a long period of time. The measured density of residue decreased in the same order to that of the diamond nucleation density. Furthermore, the ratio of the density of nucleated diamond to that of the residue decreased in the order of diamond, c-BN, SIC and lastly Al2O3. The larger the lattice difference between the residue material and diamond, the smaller the nucleation density. This result suggests that the residue of the treatment powder plays a significant role as a site for the diamond nucleation. The possibility of surface shape and defects as a nucleation site is also discussed. (C) 1997 Elsevier Science S.A.
Keywords: CHEMICAL-VAPOR-DEPOSITION; FILMS; PLASMA; GROWTH; CVD; DEFECTS